The girl who could fly - Forester, Victoria (Victoria Lakeman) (Feiwel and Friends, 2008)
Piper McCloud's ability to fly sets her apart from the other kids, so her mother sends her to an exclusive school for children with exceptional abilities, but even there she does not fit in with the other students.